Silver colloidal nanoparticles: Effect on matrix composition and structure of Candida albicans and Candida glabrata biofilms - Monteiro, D. R. [UNESP]; Silva, S.; Negri, M.; Gorup, L. F.; de Camargo, E. R.; Oliveira, R.; Barbosa, Débora de Barros [UNESP]; Henriques, M. (Oxford University Press (OUP), 2013)
Aim: The aim of this study was to assess the effect of different silver nanoparticles (SN) concentrations on the matrix composition and structure of Candida albicans and Candida glabrata biofilms. Methods and Results: Candida biofilms were developed in 6-well microtiter plates during 48 h. After, these biofilms were exposed to 13·5 or 54 μg SN ml-1 for 24 h. Then, extracellular matrices were extracted from biofilms and analysed chemically in terms of proteins, carbohydrates and DNA. To investigate the biofilm structure, scanning electron microscopy (SEM) and epifluorescence microscopy were used. SN interfered with the matrix composition of Candida biofilms tested in terms of protein, carbohydrate and DNA, except for the protein content of C. albicans biofilm. By SEM, Candida biofilms treated with SN revealed structural differences, when compared with the control groups. Further, SN showed a trend of agglomeration within the biofilms. Epifluorescence microscopy images suggest that SN induced damage on cell walls of the Candida isolates tested. Conclusions: In general, irrespective of concentration, SN affected the matrix composition and structure of Candida biofilms and these findings may be related to the mechanisms of biocide action of SN. Significance and Impact of the Study: This study reveals new insights about the behaviour of SN when in contact with Candida biofilms. SN may contribute to the development of therapies to prevent or control Candida infections. © 2012 The Society for Applied Microbiology.
Keywords: Biofilms; Candida albicans; Candida glabrata; Fungal infections; Silver nanoparticles; carbohydrate; DNA; protein; silver nanoparticle; biofilm; colloid; concentration (composition); fluorescence spectroscopy; fungus; infectivity; nanotechnology; scanning electron microscopy; silver; controlled study; epifluorescence microscopy; fungal cell wall; fungal structures; fungus isolation; microtiter plate assay; nonhuman; Candida